Dynamic Effects and Hydrogen Bonding in Mixed-Halide Perovskite Solar Cell Absorbers - Wilks, Regan G.; Erbing, Axel; Sadoughi, Golnaz; Starr, David E.; Handick, Evelyn; Meyer, Frank; Benkert, Andreas; Iannuzzi, Marcella; Hauschild, Dirk; Yang, Wanli; Blum, Monika; Weinhardt, Lothar; et al. (Journal of Physical Chemistry Letters, 2021)
The organic component (methylammonium) of CH3NH3PbI3-xClx-based perovskites shows electronic hybridization with the inorganic framework via H-bonding between N and I sites. Femtosecond dynamics induced by core excitation are shown to strongly influence the measured X-ray emission spectra and the resonant inelastic soft X-ray scattering of the organic components. The N K core excitation leads to a greatly increased N-H bond length that modifies and strengthens the interaction with the inorganic framework compared to that in the ground state. The study indicates that excited-state dynamics must be accounted for in spectroscopic studies of this perovskite solar cell material, and the organic-inorganic hybridization interaction suggests new avenues for probing the electronic structure of this class of materials. It is incidentally shown that beam damage to the methylamine component can be avoided by moving the sample under the soft X-ray beam to minimize exposure and that this procedure is necessary to prevent the creation of experimental artifacts.
CRIS-Team Scopus Importer:2021-05-14